DETERMINATION OF DIGITAL MARKETING STRATEGY WITH APPLICATION OF QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) IN ENTERPRISE RESOURCE PLANNING (ERP) SYSTEM COMPANY’S SNELL X - Rizaldi Mu'min; Jakfat Haekal; Muhammad Isa Lufti (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2022)
Marketing is one of the most important instruments in doing business, because marketing is the cornerstone of buying and selling transactions. Meanwhile, in the digital era, there have been several adjustments to marketing strategies according to market needs and behavior. Snell X is a company engaged in ERP system implementation services in companies. In developing its business, Snell X needs to do digital marketing. The method that is used on this research is the analysis of the SWOT (Strengths, Weaknesses, Opportunities and Threats), this analysis includes internal and external factors which then to be examined by numbers and ratings. The other tool that will be used is QSPM (Quantitative Strategic Planning Matrix) instruments which then examined based on what is found on SWOT matrix. Through these instruments, Snell X can determine their digital marketing strategies precisely and accurately. This research helps companies to develop digital marketing that will be carried out to build a brand image for customers. This research shows the significance of product and service development in Snell X’s advertising is rather important compared to market development.